2019
DOI: 10.1038/s41467-019-13543-1
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid signaling delimits root gravitropism via sorting of the Arabidopsis PIN2 auxin transporter

Abstract: Arabidopsis PIN2 protein directs transport of the phytohormone auxin from the root tip into the root elongation zone. Variation in hormone transport, which depends on a delicate interplay between PIN2 sorting to and from polar plasma membrane domains, determines root growth. By employing a constitutively degraded version of PIN2, we identify brassinolides as antagonists of PIN2 endocytosis. This response does not require de novo protein synthesis, but involves early events in canonical brassinolide signaling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 57 publications
6
76
1
Order By: Relevance
“…Notably, auxin itself appears to inhibit the process of endocytosis and antagonize the BFA effect on PIN recycling 15 . In addition to auxin effects on PINs, various other plant hormones can influence PIN-dependent auxin transport, such as cytokinins 23 , brassinosteroids 24,25 , gibberellins 26 , salicylic acid 27 , abscisic acid 28 , and strigolactones (SLs) 29 . However, much remains to be uncovered about the modes of action, by which these plant hormones regulate PINs, thereby ultimately defining plant development.…”
mentioning
confidence: 99%
“…Notably, auxin itself appears to inhibit the process of endocytosis and antagonize the BFA effect on PIN recycling 15 . In addition to auxin effects on PINs, various other plant hormones can influence PIN-dependent auxin transport, such as cytokinins 23 , brassinosteroids 24,25 , gibberellins 26 , salicylic acid 27 , abscisic acid 28 , and strigolactones (SLs) 29 . However, much remains to be uncovered about the modes of action, by which these plant hormones regulate PINs, thereby ultimately defining plant development.…”
mentioning
confidence: 99%
“…Some studies have indicated that exogenous BR could stimulate the biosynthesis of flavonoids in leaves 52 . Moreover, brassinolide signaling has been implicated in PIN2 sorting and intracellular distribution to delimit root gravitropism 53 . Our transcriptomic data identified the “response to brassinosteroid” and “lipid and wax metabolism” GO terms, and the endogenous brassinolide contents were increased in Pr compared to CK (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This process is exacerbated by increased auxin-dependent production of small signaling peptides GOLVEN1 ( GLV1) and GLV2 by cells on the lower side, which trigger a response pathway that also favors PIN2 association with the plasma membrane [ 99 ]. Furthermore, other phytohormones, such as the brassinosteroids and gibberellic acid, also function as antagonists of PIN endocytosis [ 100 ]. On the other hand, a long period of exposure to higher auxin levels triggers vacuolar sorting of the PIN2 protein and its vacuolar degradation, thereby potentially contributing to gradient dissipation at the end of a gravitropic response [ 66 ].…”
Section: Auxin Gradient Propagation From Root Cap To Ezmentioning
confidence: 99%
“…On the other hand, a long period of exposure to higher auxin levels triggers vacuolar sorting of the PIN2 protein and its vacuolar degradation, thereby potentially contributing to gradient dissipation at the end of a gravitropic response [ 66 ]. Hence, a complex crosstalk between hormonal signaling and PIN2 endocytic sorting contributes to regulating root gravitropic curvature [ 100 ].…”
Section: Auxin Gradient Propagation From Root Cap To Ezmentioning
confidence: 99%